Oil pollution in Vietnam and neighboring Sea - Duong, Nguyen Đinh; Thu, Ho Le; Anh, Le Van; Anh, Nguyen Kim (Vietnam Journal of Earth Sciences, 2014)
Vietnam and neighboring Sea is one of the regions which own amount of oil resources in the world. Currently, exploration and exploitation is being promoted not only in shallow water but also increasingly expanded in deeper water.In addition, East Sea is the place where is available high density of major transportation routes in the world. Due to the impact of these activities, oil pollution in the sea is inevitable. Marine oil pollution causes by drilling and exploring operations, drilling problems especially illegal discharge of oil tankers. In order to timely detection and early warning ofthe oil spill and illegal discharge cases, microwave remote sensing has been used in many countries in the world. Being able to obtain in all weather conditions as well as day and night time, microwave remote sensing data can provide information about sea surface over a large area with suitable resolution which is considered as an effective tool for monitoring oil pollution in the sea. In this paper, authors present research which conducted application of microwave remote sensing data in detection of oil spill in Vietnam and East Sea. Based on process and analysis of ALOS PALSAR satellite data in ScanSAR mode acquired in 2008 and 2009, the authors established map of oil pollution risk over the study area and drew out some first conclusion about rule of spatial distribution of oil pollution in Vietnam and neighboring Sea.